Production of mannooligosaccharides from pineapple pulp and pine sawdust using Aspergillus niger derived Man26A and determination of their prebiotic effect - Hlalukana, Nosipho Pretty (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology)
Lignocellulosic biomass is the most abundant source of renewable biomass on earth. Lignocellulosic biomass consists of cellulose, hemicelluloses and lignin. These can be used as a source of renewable fuel as well as other value-added products . Mannans are part of the hemicellulose fraction of lignocellulosic biomass and are the major hemicellulosic polysaccharide fraction in softwoods, where they are found as galactoglucomannans and as glucomannans. Mannans are also found in hardwoods in the form of glucomannans. Mannans can be enzymatically hydrolysed using endo-mannanases to produce of short chain mannooligosaccharides (MOS). MOS have received significant attention for their prebiotic properties, as they promote the growth of probiotic bacteria, which have positively affects on gut health. This study focused on the production of prebiotic MOS from lignocellulosic biomass waste (LBW) and an evaluation of the prebiotic potential of the produced MOS. An Aspergillus niger derived endo-mannanase, Man26A, was fractionated and biochemically analysed. Purified Man26A had a fold purification of 1.25 and a yield of 41.1%. SDS-PAGE analysis of the enzyme revealed that it had a molecular weight of 46 kDa. The pH and temperature optima of Man26A were determined and the pH optimum was found to be pH 4.0 (but the enzyme displayed high activity over a broad acidic pH range, with up to 90% of the activity retained between pH 3.0 and 7.0). The temperature optimum was 50℃. The enzyme was shown to have the highest specific activity on locust bean gum (52.27 U/mg) and ivory nut mannan (57.25 U/mg), compared to guar gum (29.07 U/mg), which indicated that it was affected by the substitution pattern of the mannans. Man26A produced MOS of different diversity on model mannan substrates, where the MOS produced were mannobiose, mannotriose, and mannotetraose for ivory nut mannan, mannobiose, mannotriose, mannotetraose, and mannopentaose and MOS with a higher degree of polymerisation for locust bean gum, and mannobiose, mannotriose, mannotetraose, mannopentaose, and mannohexose and MOS with a higher degree of polymerisation for guar gum, as determined by thin layer chromatography (TLC) and high-performance liquid chromatography (HPLC). Pretreatment and characterisation of pineapple pulp (PP) and pine sawdust (PSD) was conducted, and the impact of the pretreatment procedures was analysed using Megazyme sugar kits, thermogravimetric analysis (TGA), Fourier-transform infrared spectroscopy (FTIR), and microscopic analysis using scanning electron microscopy (SEM) and light microscopy. Compositional analysis of the carbohydrates present in both substrates revealed that they had a glucan content of 36.41 and 50.47% for untreated PP and PSD, respectively. Their respective mannan content was 6.74 and 11.59% and was deemed sufficient for the production of MOS via enzymatic hydrolysis. TGA analysis revealed that untreated and sodium chlorite-acetic acid delignified samples decomposed at approximately the same time, and had a negligible ash content at 600℃, while delignified plus phosphoric acid swollen substrates decomposed at a faster rate, but had a residual ash content at 600℃. FTIR analysis of the substrates revealed slight changes in the structures of untreated and pretreated samples. SEM analysis of PP and PSD showed a change in the morphology of the substrates with subsequent pretreatment steps. Histochemical analysis for lignin for PP and PSD showed successful delignification upon pretreatment. Untreated and sodium chlorite delignified PP and PSD released low amounts of reducing sugars compared to delignified + phosphoric acid swollen substrates. The delignified + phosphoric acid swollen substrates were used for further experiments. MOS produced from delignified and phosphoric acid swollen (Del + PAS) PP and PSD at 0.1 mg/ml enzyme loading and 80 mg/ml (8% (w/v)) substrate concentration, ran between mannose and mannobiose and between mannobiose and manotriose on TLC, with low concentrations of MOS running between mannotetraose and mannopentaose. HPLC analysis of the MOS revealed that Del + PAS PP produced mannose to mannohexose, while Del + PAS PSD produced mannose, mannobiose, and mannotetraose. The MOS were analysed using FTIR, to determine whether the MOS produced contained any acetyl groups, which were present for Del + PAS PSD at 1706 cm-1. The MOS were stable at different pHs, and at temperatures below 200℃. The MOS were also found to be stable in a simulated gastrointestinal environment, in the presence of bile salts and digestive enzymes. The prebiotic effect of the MOS derived from Del + PAS PP and PSD was evaluated. MOS had a proliferative effect on probiotic bacteria (Lactobacillus bulgaricus, Bacillus subtilis and Streptococcus thermophilus). The production of short chain fatty acids (SCFAs) was evaluated on TLC, where no SCFAs were observed on the plate. The effect of MOS on the adhesion ability of bacteria revealed that they do not positively influence the adhesion of probiotic bacteria. The antioxidant activities of 1 mg/ml MOS produced from both substrates were determined to be approximately 15% using the ABTS radical scavenging assay, compared to a radical scavenging activity of 45% for the 0.02 mg/ml gallic acid standard. This study demonstrated that biomass waste could be used to produce prebiotic MOS, which play a positive role in gut ecology and provide health benefits.
Keywords: Oligosaccharides; Prebiotics; Lignocellulose; Mannans